Determination of Platinum-Group Elements and Re-Os Isotopes using ID-ICP-MS and N-TIMS from a Single Digestion after Two-Stage Column Separation - Li, J.; Jiang, X.; Xu, J.; Zhong, L.; Wang, Xuan-Ce; Wang, G.; Zhao, P. (Wiley-Blackwell Publishing, 2014)
We report an improved procedure for the determination of the platinum-group elements (PGE) and Re, and Os isotopes from a single sample aliquot by isotope dilution (ID) using inductively coupled plasma-mass spectrometry (ICP-MS) and negative thermal ionisation mass spectrometry (N-TIMS), respectively. A two-stage column method was used to purify PGE-Re from their samplematrix and interfering elements (e.g., Mo, Zr and Hf) after Os had been separated by CCl4 solvent extraction. The first column separation step used cation exchange resin (AG50W-X8) to concentrate PGE-Re and some potential interfering elements (e.g., Mo, Zr and Hf). In the second step, N-benzoyl-N-phenylhydroxylamine (BPHA) extraction resin was used to separate PGE-Re from the remaining interfering elements, which all remained strongly absorbed to the resin. The method was used todetermine the PGE and rhenium, and Os isotope ratios in a range of geochemical reference materials (TDB-1, WGB-1, BHVO-2 and UB-N). The obtained results agree well with those previously published. This new method enables PGE-Re abundances and Os isotopic ratios to be determined on the same sample digestion, and circumvents the problems created by sample heterogeneity when comparing PGE and Re-Os isotope data.